1992
DOI: 10.1159/000133336
|View full text |Cite
|
Sign up to set email alerts
|

Sublocalization of an invasion-inducing locus and other genes on human chromosome 7

Abstract: By somatic cell fusion studies between noninvasive mouse T-lymphoma cells and invasive human activated normal T-cells we have previously shown that the genetic information responsible for the induction of invasive and metastatic potential in interspecies T-cell hybrids is located on human chromosome 7. Apparently, genes derived from normal activated T-cells are dominantly expressed in the hybrids and control the invasive and, as a consequence, metastatic potential of these T-lymphoma cells. To sublocalize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The map of the latter amplification unit includes the gene of the epidermalgrowth-factor receptor, EGFR (Habets et al, 1992). FISH with an EGFR cDNA probe labels the proximal three quarters of the HSR of marker 1 (results not shown), which is in line with the hybridization results obtained with the WCP 7 probe (Fig.…”
Section: Candidate-gene Approach For the Amplified Region 7p11-p12supporting
confidence: 80%
See 1 more Smart Citation
“…The map of the latter amplification unit includes the gene of the epidermalgrowth-factor receptor, EGFR (Habets et al, 1992). FISH with an EGFR cDNA probe labels the proximal three quarters of the HSR of marker 1 (results not shown), which is in line with the hybridization results obtained with the WCP 7 probe (Fig.…”
Section: Candidate-gene Approach For the Amplified Region 7p11-p12supporting
confidence: 80%
“…The putative target of the amplification of 7p11-p12 was the gene for the epidermal-growth-factor receptor, EGFR (Neal et al, 1990;Habets et al, 1992). FISH analysis with an EGFR-specific cDNA probe on tumor chromosomes (results not shown), semi-quantitative PCR and Northern blot analysis (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Also, gain of chromosome arm 7p, known to harbor epidermal growth factor receptor (EGFR) and T-cell tumor invasion and metastasis-1 (TTIM1) genes (Kondo and Shimizu, 1983), was frequently found (8/12) in primary tumors and/or their metastases. Somatic cell fusion studies (Collard et al, 1987;Habets et al, 1992) have shown that the invasive capabilities of hybrid cells depended on the presence of chromosome fragment 7p12-cen.…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR gene is 110 kb in size, has 26 exons and is located on chromosome 7p12 [Habets et al, 1992]. The ®rst intron, which is the focus of our studies, is 18 kb in size.…”
mentioning
confidence: 92%